PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN DARING DI APLIKASI SHOPEE PADA MAHASISWA DI KOTA PADANG - Maizul Rahmizal; Rido Yuvendri (JURNAL PUNDI, 2020)
Fast traslate Icon translate     Fast traslate Icon translate Online purchasing decisions are a process for consumers to make purchases through an alternative process using the internet media which has very high value benefits. The purpose of this study was to examine the effect of trust, convenience and quality of information on online purchasing decisions in the shopee application among students in the city of Padang. This type of research is a quantitative approach, with a population of students in the city of Padang who have made online purchases in the Shopee application totaling 96 samples using the lemeshow formula measurement. The data analysis technique used instrument test, classical assumption test, and multiple linear regression. The data were processed using multiple linear regression using a questionnaire. The results of this study indicate that the trust, convenience and quality of information partially have a significant effect on online purchasing decisions in the shopee application for students in the city of Padang.